Challenges facing promotion of teachers in public secondary schools: The case of Ilemela municipal council - Mwijage, Denis (Mzumbe University, 2024)
A dissertation submitted in partial fulfillment of the requirements for the award of Degree of Masters of Science in Human Resource Management (MSc-HRM) of Mzumbe University